2013
DOI: 10.4028/www.scientific.net/amr.734-737.819
|View full text |Cite
|
Sign up to set email alerts
|

Study on Characteristic and Mechanism of Deformation and Failure of Roadway Surrounding Rock in Deep Mining

Abstract: In order to study the mechanics of the deformation of the wall rock, the right roadway in Chengshan mining field, Jixi Mine was chosen to determine the physical property, micro-structure, ingredients, clay and the inner-relationships between these properties using scanning electron microscope (SEM) and theoretical analysis. For further understanding the deformation mechanics within the wall rock, hollow inclusion stress release method was used. At the end, mechanism of the wall rock in the deep was established… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Overburden fracture is the channel of water seepage, migration and water storage space. The seepage disaster process of rock strata is the result of the coupling effect of a water-bearing body and consolidated rock mass [17]. According to the deformation and instability process of roof strata, the elastic theory of pore-fissure is referred to [18][19][20][21], and the water inrush process of coal seam mining is divided into three "solid-liquid" coupling action stages:…”
Section: "Solid-liquid" Coupling Water Inrush Mechanism In Coal Seam ...mentioning
confidence: 99%
“…Overburden fracture is the channel of water seepage, migration and water storage space. The seepage disaster process of rock strata is the result of the coupling effect of a water-bearing body and consolidated rock mass [17]. According to the deformation and instability process of roof strata, the elastic theory of pore-fissure is referred to [18][19][20][21], and the water inrush process of coal seam mining is divided into three "solid-liquid" coupling action stages:…”
Section: "Solid-liquid" Coupling Water Inrush Mechanism In Coal Seam ...mentioning
confidence: 99%
“…It is a significant piece of infrastructure, and its establishment is the most challenging project related to underground mine construction. Compared with a shallow shaft, the geological conditions and stress state of a deep shaft are more complex, especially under the action of strong excavation disturbance (Li et al 2013;Walton et al 2018). Polytropic strata and stress conditions produce increasingly complicated mechanical response mechanisms and distinct response characteristics as depth increases (Mishra et al 2017;Li et al 2020;Zhang et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Practice has demonstrated that whether an anchor can provide sufficient pre-tightening force is key to realizing active support, effectively controlling the deformation of the surrounding rock in the roadway, and improving the anchor supporting quality in the deep roadway, especially in roadway support under broken rock mass conditions. Grouting anchor measures can effectively improve the integrity of the surrounding rocks in the roadway and effectively enhance the cohesion and internal friction angle of the surrounding rocks [1] [2] [3] [4], thereby increasing the selfsupporting ability of the surrounding rocks and significantly improving the roadway-supporting effect and quality. However, because the length of the free segment of the grouting anchor is usually quite short, the application of pre-tightening force is very limited [5] [6] [7], which fails to meet the demand of active support.…”
Section: Introductionmentioning
confidence: 99%